Analisis Faktor Penyebab Anak Remaja Kecanduan Bermain Game Online - Ade Kasantarino; Lalu Ahmad Taubih (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Online games are a type of video game that can only be run if a device used to play games is connected to an internet network. So, if someone wants to play online games, the device he uses must be connected to the internet network. If not, then it is very likely that online games cannot be played. Online game addiction is a type of addiction caused by internet technology. The internet can cause addiction, one of which is Computer Game Addiction (playing games excessively). Online games are part of the internet that are frequently visited and are very popular and can cause addiction that has a very high intensity. The research objective of the problems to be achieved through this research is to find out the factors that cause teenagers to be addicted to playing online games in Orong Bawa Village. The research used in this research is descriptive qualitative, namely describing data as it is and explaining data or events with qualitative explanations, expressed through qualitative methods. From the results the researchers analyzed that in this study there were also the author can draw the conclusion that there are several young informants in Deisa Orong Bawa Utan District who can be an illustration based on the theory used by researchers as a reference, namely where to use intrapersonal communication, interpersonal communication and group communication. The addiction factor for playing online games is influenced by 2 factors as already explained that these factors are internal factors including self-will, feeling bored, unable to set priorities and lack of self-control and external factors include unfavorable environment, not having social relationships with people old.